THE FACTORS INFLUENCING CONSUMER BEHAVIOR IN INDOMARET POTANGA SUB-DISTRICT, BARAT CITY, GORONTALO CITY - Amna Latif; Frista Iin Wahyuni; Nuzmerini Rauf (LP2M Universitas Bina Mandiri Gorontalo, 2022)
This study aims to find how are the factors that influencing Indomaret Consumer Behavior in Potanga Village, Kota Barat District, Gorontalo City. The research method used is the primary data approach with reference to quantitative research. The pupolation and sample in this study were 100 consumers at one of the Indomaret Sub-Districts of techniques using observation, questionnaires and documentation. Obtained from the calculation of the questionnaire that will the carried out which relates to research problems with the analytical method using simple regression. The results of the study are that consumers (X) have a significant effect on consumer behavior (Y) with the result that the t-count value for the variable factors is 30, 705 with a significance value of 0.000. this significance value is still smaller than the alpha value (0,05) so that Ho is rejected. In other words, at the 95% confidence level, it can be concluded that there is a positive and significant influence of these factors on consumer behavior in Indomaret, Potanga Village, Kota Barat Distict, Gorontalo City.